Effects of salt stress on ion balance and nitrogen metabolism of old and young leaves in rice (Oryza sativa L.) - Wang, Huan (BioMed Central, 2012)
BACKGROUND: It is well known that salt stress has different effects on old and young tissues. However, it remains largely unexplored whether old and young tissues have different regulatory mechanism during adaptation of plants to salt stress. The aim of this study was to investigate whether salt stress has different effects on the ion balance and nitrogen metabolism in the old and young leaves of rice, and to compare functions of both organs in rice salt tolerance. RESULTS: Rice protected young leaves from ion harm via the large accumulation of Na(+) and Cl(−) in old leaves. The up-regulation of OsHKT1;1, OsHAK10 and OsHAK16 might contribute to accumulation of Na(+) in old leaves under salt stress. In addition, lower expression of OsHKT1;5 and OsSOS1 in old leaves may decrease frequency of retrieving Na(+) from old leaf cells. Under salt stress, old leaves showed higher concentration of NO(3)(−) content than young leaves. Up-regulation of OsNRT1;2, a gene coding nitrate transporter, might contribute to the accumulation of NO(3)(−) in the old leaves of salt stressed-rice. Salt stress clearly up-regulated the expression of OsGDH2 and OsGDH3 in old leaves, while strongly down-regulated expression of OsGS2 and OsFd-GOGAT in old leaves. CONCLUSIONS: The down-regulation of OsGS2 and OsFd-GOGAT in old leaves might be a harmful response to excesses of Na(+) and Cl(−). Under salt stress, rice might accumulate Na(+) and Cl(−) to toxic levels in old leaves. This might influence photorespiration process, reduce NH(4)(+) production from photorespiration, and immediately down-regulate the expression of OsGS2 and OsFd-GOGAT in old leaves of salt stressed rice. Excesses of Na(+) and Cl(−) also might change the pathway of NH(4)(+) assimilation in old leaves of salt stressed rice plants, weaken GOGAT/GS pathway and elevate GDH pathway.